Dietary micronized hemp fiber enhances in vitro nutrient digestibility and cecal fermentation, antioxidant enzyme, lysosomal activity, and productivity in finisher broilers reared under thermal stress - Incharoen, Tossaporn; Nopparatmaitree, Manatsanun; Kongkeaw, Adisak; Soisuwan, Keatisak; Likittrakulwong, Wirot; Thongnum, Atichat; Norbu, Nima; Tenzin, Jigme; Supatsaraphokin, Natphapat; Loor, Juan J. (Frontiers in Animal Science, 2025)
IntroductionHeat stress impairs broiler performance and exacerbates oxidative stress. Hemp (Cannabis sativa L.) contains cannabidiol (CBD) and other bioactive compounds with antioxidant, anti-inflammatory, and immunomodulatory properties, which may enhance health status and overall performance in broilers. This study aimed to investigate the effects of dietary micronized hemp fiber (MHF) supplementation on in vitro nutrient digestibility, cecal fermentation, antioxidant enzyme activity, lysosomal function, and productivity in finisher broilers reared under a thermal environment.MethodsAt 21 days of age, 210 broilers with uniform body weight were randomly allocated to three dietary treatments: a basal diet (CON), and diets supplemented with MHF at 0.75% (L-MHF) or 1.50% (H-MHF). Birds had ad libitum access to diets until 42 days of age.ResultsCompared with the CON, there was no effect (p > 0.05) of MHF supplementation on in vitro true digestibility of dry matter, organic matter, crude protein, ether extract, or gross energy. Similarly, gas production at various incubation times and the rate and extent of gas production from cecal fermentation did not differ (p > 0.05). However, cecal fermentation analysis revealed that total volatile fatty acid (VFA) concentrations, including acetic, propionic, and butyric acids, were significantly higher (p < 0.01) in the L-MHF and H-MHF groups. Microbiological analysis revealed increased (p < 0.01) total bacterial counts, lactic acid bacteria, and Enterococcus sp. populations, coupled with reduced E. coli counts in the L-MHF and H-MHF groups. There was a significant (p < 0.001) improvement in final body weight and average daily gain in the H-MHF group compared with the CON and L-MHF groups. Feed conversion ratio was lowest (p < 0.001) in the H-MHF group across all measured periods, while average daily feed intake remained unaffected (p > 0.05). Except for increased (p < 0.05) wing weight in the H-MHF group, dressing percentage or weight of major cuts did not differ (p > 0.05). Antioxidant enzyme activity was enhanced in the MHF-groups, with higher (p < 0.001) catalase, superoxide dismutase, and glutathione peroxidase activities observed in the H-MHF and L-MHF groups. However, lysozyme activity was reduced (p < 0.05) in the H-MHF group.ConclusionDietary supplementation with MHF improved in vitro cecal fermentation profiles, antioxidant capacity, and productivity metrics in finisher broilers under thermal stress. These findings underscore the potential of MHF as a functional feed additive in broiler production.